2015
DOI: 10.1002/lno.10160
|View full text |Cite
|
Sign up to set email alerts
|

Differential carbon utilization and asexual reproduction under elevated pCO2 conditions in the model anemone, Exaiptasia pallida, hosting different symbionts

Abstract: Here we report the effects of elevated pCO2 on the model symbiotic anemone Exaiptasia pallida and how its association with three different strains of the endosymbiotic dinoflagellate Symbiodinium minutum (ITS2‐type B1) affects its response. Exposure to elevated pCO2 (70.9 Pa) for 28 d led to an increased effective quantum yield of PSII in actinic light within two of the alga‐anemone combinations. Autotrophic carbon fixation, along with the rate of carbon translocated to the animal, were significantly elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 80 publications
3
24
0
Order By: Relevance
“…However, if mitochondrial copy number ratio is heritable (Ding et al, 2015 ), this variability may reflect a high genetic diversity within our E. pallida population. Preliminary analysis of microsatellite loci as described by Hoadley et al ( 2015 ) suggested that at least 60% of our anemones were genetically distinct individuals (data not shown). Likewise, anemone size was also highly variable in our natural population (range 0.1–2.0 mg total soluble protein) and mtDNA/nucDNA can vary with age (Simonetti et al, 1992 ; Barazzoni et al, 2000 ).…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…However, if mitochondrial copy number ratio is heritable (Ding et al, 2015 ), this variability may reflect a high genetic diversity within our E. pallida population. Preliminary analysis of microsatellite loci as described by Hoadley et al ( 2015 ) suggested that at least 60% of our anemones were genetically distinct individuals (data not shown). Likewise, anemone size was also highly variable in our natural population (range 0.1–2.0 mg total soluble protein) and mtDNA/nucDNA can vary with age (Simonetti et al, 1992 ; Barazzoni et al, 2000 ).…”
Section: Discussionsupporting
confidence: 49%
“…Novel E. pallida-Symbiodinium associations were established by exposing aposymbiotic anemones to one of two different Symbiodinium species (~1000 cells mL −1 in 500 mL seawater) according to the methods of Hoadley et al ( 2015 ). One group ( n > 30 animals) was incubated with a homologous, monoclonal Symbiodinium culture established from Symbiodinium originally isolated from the same E. pallida population and maintained in semi-continuous growth in f/2-Si culture media (Guillard, 1973 ) for period of at least 1 year.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding increase in Symbiodinium P gross was somewhat surprising, as it occurred while F v /F m dropped. This could reflect the release of remaining Symbiodinium cells from carbon limitation as in hospite symbionts declined (Hoadley et al, 2015). Equally, it might have resulted in part from positive effects of heating on the rate of Symbiodinium A4 Rubisco activity (Galmés et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Photosynthetic responses retrieved from fluorometricand O 2 -based measurements provide insight into Ci uptake efficiency (Brading et al 2011;Oakley et al 2014;Roberty et al 2014;Suggett et al 2015;Grégoire et al 2017), yet few direct Ci assimilation rates have been performed to date despite early foundational work on coral endosymbionts (Al-Moghrabi et al 1996;Goiran et al 1996;Allemand et al 1998). More recent studies on Ci assimilation have adopted diverse approaches using stable ( 13 C; Pernice et al 2014;Baker et al 2018;Krueger et al 2018;Radecker et al 2018) and radioisotope methods ( 14 C; Brading et al 2013;Hoadley et al 2015Hoadley et al , 2016. As such, methodological differences across studies such as variable incubation lengths (Halsey et al 2013;Hughes et al 2018b) limit any reconciliation across species and environmental treatments.…”
mentioning
confidence: 99%